Comparison between conventional open-heart valve surgery and minimally invasive valve replacement surgery regarding the length of hospital stay and usage of blood derivates: insights from a single-centre, single-surgeon study conducted in Bosnia and Herzegovina - Nermir Granov; Amel Hadžimehmedagić; Armin Šljivo; Tarik Selimović; Damir Kurtagić; Edin Kabil; Muhamed Djedović; Arian Abdulkhaliq (Medicinski glasnik, 2023)
Aim: To analyse the correlation between different surgical methodologies employed in valve diseases treatment and their subsequent impact on the duration of hospitalization. Methods: This retrospective study conducted at the Clinical Centre of the University of Sarajevo analysed medical records of 163 valve disease patients treated between January 2019 and November 2022. The patients were divided into two groups: 77 had openheart valve surgery and 86 underwent minimally invasive cardiac surgery (MICS). Results: The mean duration of the surgical procedures was 3.9±1.3 hours, with conventional open-heart surgery requiring an average of 3.6±1.1 hours and minimally invasive cardiac surgery (MICS) procedure 4.2±1.5 hours. No substantial disparities were found in the total length of hospitalization between the two groups, as both conventional (8.2±4.5 days) and MICS (8.7±7.0 days) demonstrated similar duration. Similarly, the total duration of intensive care unit (ICU) stay displayed similarity, with conventional surgery patients staying an average of 3.9±2.8 days and MICS patients of 4.2±4.1 days. The pattern of blood transfusion and fresh-frozen plasma usage revealed higher rates in the conventional valve surgery group comparing to the MICS group. Conclusion: Minimally invasive valve surgery, despite slightly longer operative times, resulted in lower blood transfusion requirements and comparable hospitalization and ICU stay.
Keywords: blood; Bosnia and Herzegovina; cardiovascular surgical procedures; heart valves; minimally invasive surgical procedures